CFD Simulation of CO2 and Methane Adsorption at Various Temperature for MOF-5 using Dual-site and Single-site Langmuir Model - Zulkifli M.Z.A.; Mukhtar A.; Fadli M.F.M.; Bahari A.M.S.; Matsumoto A.; Misran H. (Penerbit Akademia Baru, 2023)
The annual increase in energy demand has led to an increase in greenhouse gas emissions, in particular CO2 emissions from the power generation industry. Carbon Capture and Utilization are technologies applied to capture CO2 gases and transform the gases into a different energy source. The adsorption technology to capture CO2 gases was chosen due to the minimum energy consumption and low costs required for an industrial application for sustainability. Metal-Organic Framework (MOF) has a reasonably high CO2 adsorption capability. It has been applied as an adsorbent for capturing and storing CO2. In this study, a comparison of CFD simulation with experimental CO2 and methane adsorption values in solid adsorbent beds containing MOF-5 at various temperatures was presented. The simulation was performed using 2D and 3D models from 0? at STP to 130? for CO2 and methane gas molecules. In addition, the isothermal and kinetic adsorption model was added to the simulations. This includes Single-and Dual-Site Langmuir adsorption isotherm and Linear Driving Force. The porous media model was then activated to imitate packed bed adsorbent and measured the pressure drop from the simulation. The results showed that the CO2 adsorption values of MOF-5 decrease as the adsorbent temperature increases. There was a decline of 0.002 mmol/g of adsorbed CO2 molecules per 10-kelvin difference. The CO2 adsorption value was 0.53 mmol/g at STP and 1.15 mmol/g for CH4 at STP. Both CO2 and CH4 adsorption were used to suggest optimal CO2 adsorption for the Pressure Swing Adsorption cycle. 2021, Penerbit Akademia Baru. All rights reserved.